Antioxidant and anti-inflammatory properties of sourdoughs containing selected Lactobacilli strains are retained in breads. (30th August 2020) - Luti, Simone; Mazzoli, Lorenzo; Ramazzotti, Matteo; Galli, Viola; Venturi, Manuel; Marino, Giada; Lehmann, Martin; Guerrini, Simona; Granchi, Lisa; Paoli, Paolo; Pazzagli, Luigia
Highlights: Three Lactobacilli strains are very active in producing bioactive peptides. Peptides from breads are equipped with antioxidant and anti-inflammatory activity. Sequences of peptides both from doughs and breads have been determined. In spite of differences in peptide sequences, biological activity is preserved. Abstract: Sourdough fermentation influences several properties of leavened baked goods also because Lactic acid bacteria (LAB) and yeasts produce bioactive peptides with a positive effect on human health. In an early study, three Lactobacilli strains ( L. farciminis H3 and A11 and L. sanfranciscensis I4) possessing different proteolytic activities were used to produce sourdoughs containing peptides equipped with anti-inflammatory and/or antioxidant properties. This work was aimed to assess whether these properties could be retained after cooking. The selected LABs were used to produce breads from which low molecular weight (LMW-) peptides were extracted. The results provide solid proofs of keeping both antioxidant and anti-inflammatory activities of peptides from cooked products. Sequences of LMW-peptides either from doughs and breads were determined by mass spectrometry: differences have been noticed in amino acidic composition and in sequences, however, all the strains produce peptides equipped with antioxidant and anti-inflammatory activities.